Individual perspectives and mental maps of working conditions and intention to stay of physicians in academic medicine - Hasebrook, Joachim; Hecke, Juliane; Volkert, Thomas; Singer, Maren; Hinkelmann, Juergen; Michalak, Leonie; Hahnenkamp, Klaus (Frontiers in Psychology, 2023)
Job satisfaction has a strong impact on the intention to stay which is an important aspect to counter skills shortage in academic medicine. In an interview study combining qualitative and quantitative methods, we investigated how the individual mental representation of working conditions influences job satisfaction and its impact on the intention to stay. In a first study, chief physicians participated in interviews about job satisfaction in academic hospitals. Answers were segmented into statements, ordered by topics, and rated according to their valence, that is, positive and increasing job satisfaction or negative and decreasing job satisfaction. In a second study, assistant physicians (residents) during and after their training period talked about strengths, weaknesses, and potential improvements of working conditions. Again, answers were segmented, ordered, rated, and used to develop a ‘satisfaction scale’. In a third study, physicians participated in a computer-led repertory grid procedure composing ‘mental maps’ of job satisfaction factors, filled in the job satisfaction scale and rated if they would recommend work and training in their clinic as well as their intention to stay. Comparing the interview results with recommendation rates and intention to stay show that high workload and poor career perspectives are linked to a negative attitude. A positive attitude towards work environment and high intention to stay is based on sufficient personnel and technical capacities, reliable duty scheduling and fair salaries. The third study using repertory grids showed that the perception of current teamwork and future developments concerning work environment were the main aspects to improve job satisfaction and the intention to stay. The results of the interview studies were used to develop an array of adaptive improvement measure. The results support prior findings that job dissatisfaction is mostly based on generally known ‘hygiene factors’ and whereas job satisfaction is due to individual aspects.